2015
DOI: 10.3402/ljm.v10.26875
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of arsenite (As+3)-induced acute cytotoxicity in human cervical epithelial carcinoma cells

Abstract: BackgroundRapid industrialization is discharging toxic heavy metals into the environment, disturbing human health in many ways and causing various neurologic, cardiovascular, and dermatologic abnormalities and certain types of cancer. The presence of arsenic in drinking water from different urban and rural areas of the major cities of Pakistan, for example, Lahore, Faisalabad, and Kasur, was found to be beyond the permissible limit of 10 parts per billion set by the World Health Organization. Therefore the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The observed cellular deformities included extensive vacuolation, contact loss, cell rounding and lysis. These cellular alterations may have been attributable to reactiveness of metal cations and generation of ROS . These researchers’ findings indicate that at higher concentrations NPs react with biomolecules and produce ROS, leading to the cell death.…”
Section: Discussionmentioning
confidence: 89%
“…The observed cellular deformities included extensive vacuolation, contact loss, cell rounding and lysis. These cellular alterations may have been attributable to reactiveness of metal cations and generation of ROS . These researchers’ findings indicate that at higher concentrations NPs react with biomolecules and produce ROS, leading to the cell death.…”
Section: Discussionmentioning
confidence: 89%
“…The BAX, caspase 3 and caspase 9 protein are generally related with the intrinsic apoptotic pathway (Dewson and Kluck 2009 ). In several other studies, it has also been reported that altering Bcl-2 family proteins and activating the intrinsic pathway are induced for apoptosis in human mesenchymal stem cells (Yadav et al 2010 ) and cytotoxic effect through the activation of the intrinsic caspase-dependent apoptotic pathway is displayed in the human epithelial carcinoma cell line treated with arsenite (Arshad et al 2015 ). Besides, we have demonstrated that the increased stress-related proteins, such as p21, HSP 70 and HSP 90, are also observed by SMA treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Besides, we have demonstrated that the increased stress-related proteins, such as p21, HSP 70 and HSP 90, are also observed by SMA treatment. The expression level of p21 was increased by arsenite treatment in the human epithelial carcinoma cells (Arshad et al 2015 ). And the increased p21 protein also induced the intrinsic apoptosis pathway and arrest of cell cycle (Cao et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%